Investing in the stock market - Hambrick, Marion E. (SAGE Business Cases., 2020)
A 2018 Gallup poll found that most Americans younger than 35 typically do not invest in the stock market. Reasons for this decision include the Great Recession and accompanying stock market decline, as well as more recent volatility in the stock market. Research, however, suggests investors can obtain the largest capital gains by purchasing stocks versus other investment options such as bonds, certificates of deposit, and gold. This case presents a scenario about a new investor and the path she takes to learn about the stock market and make her initial foray into investing. Included in the case are basic information about investing in the stock market, starting with information about what a stock is as well as what advantages and disadvantages stocks offer investors and the companies issuing them. Readers are asked to review background information about the stock market, details about financial statements and financial ratios, and evaluate three stocks offered by publicly traded sports organizations.